Capacity of Fox's H-function Fading Channel with Adaptive Transmission - Rahama, Yousuf Abo (2016)
Novel closed-form exact expressions for the capacity of the recently-introduced Fox's H-function fading channel are derived. The expressions are obtained assuming different types of adaptive transmission strategies, namely, channel inversion with fixed rate (CIFR), truncated channel inversion with fixed rate (TIFR), optimum rate adaptation with fixed power (ORA) and optimum power and rate adaptation (OPRA). The obtained expressions are versatile and can be used to evaluate the capacity for virtually any fading channel one might be interested in as a special case.